The Effect of Profitability, Corporate Social Responsibility, Independent Commissioner and Audit Committee on Tax Avoidance (Study on Mnaufaktur Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2017-2021) - Karimah Budiaty; angela dirman (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
This study aims to analyze the effect of profitability, corporate social responsibility, independent commissioners, and audit committee decision case studies in manufacturing companies consumer goods industry sector listed onthe Indonesian stock exchange in 2017-2021. In this study has 5 variables used, namely tax avoidance as a dependent variable while profitability, corporate social responsibility, independent commissioners, and audit committee as independent variables. This study used secondary data with using the purposive sampling method. The sample used in this study were 34 companies. The data analysis used for this test is multiple linear regression analysis with SPSS version 25 program. Based on the result of this study it was found that profitability has a positive effect significant effect on tax avoidance. Corporate Social Responsibility has a negative significant effect on tax avoidance. Independent commissioners has no significant effect on tax avoidance and audit committee has no significant effect on tax avoidance.